Analisis Pendapatan Pengusaha Tas Anyaman Rotan (Anjat) Di Kampung Pepas Eheng Kecamatan Barong Tongkok Kabupaten Kutai Barat - Vincensius Rinaldi; Muhammad Saleh; Diana Lestari (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2019)
Abstract, Analysis of the income of the entrepreneur Rattan woven bags  in the Eheng subdistrict of Pepas Barong Tongkok West Kutai Regency. Guidance Mr. Muhammad Saleh and Mrs. Diana Lestari.The purpose of this research is to know what is the average income of the entrepreneur rattan woven bags (anjat) in the Eheng subdistrict of Pepas Barong Tongkok West Kutai Regency.Primary data obtained directly in the field by means of surveys and interviews with employers directly in field anjat rattan bag example using a list of questions that are already in the set. Secondary data can be from various institutions and agencies related to the research and literature related to this research.After completion, the average wicker rattan bag businessman is Rp 2,914,833 per month, and has fulfilled the needs of a decent living (KHL).